Crazy house [compact disc, unabridged] - Patterson, James, 1947-; Charbonnet, Gabrielle (Hachette Audio, 2017)
In a future world where teenagers are taken, imprisoned, and forced to fight for their survival, well-behaved Cassie will do whatever it takes to save her rebellious twin sister from Death Row.